ESKALASI BISNIS KULINER MELALUI LITERASI DIGITAL DI SENTRA WISATA KULINER KOTA SURABAYA - Rachmad Ari Fattah; Ike Marcelia Harianto; Windijarto Windijarto (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
This study examines how digital marketing literacy boosts culinary SMEs' income by optimizing digital platforms to expand reach and attract customers, addressing current gaps in digital skills among food stall owners in culinary tourism centers. This research uses a mixed-method approach combining interactive training, FGDs, and multi-stakeholder talkshows to comprehensively analyze digital marketing adoption and its revenue impact on culinary SMEs in tourism centers. The program successfully enhanced culinary SMEs' digital capabilities in Google Business and food delivery platforms through targeted training, collaborative talkshows, and practical case studies, overcoming adoption barriers and driving business growth. The program successfully enhanced culinary SMEs' digital capabilities in Google Business and food delivery platforms through targeted training, collaborative talkshows, and practical case studies, overcoming adoption barriers and driving business growth.